High Risk Behaviour Tertular HIV/AIDS pada Anak Buah Kapal - Mansur Sididi; Rahman Rahman; Yusriani Yusriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to analyze the factors that influence the high risk behavior of contracting HIV / AIDS on ship crews in Makassar City. This type of research is a quantitative study with a cross sectional study design. The results showed that there was no influence of knowledge and support from health workers with the high risk behavior of contracting HIV / AIDS on ship crew at Soekarno-Hatta Port because crew members already know a lot about transmission from HIV / AIDS and are also supported by the education level of ABK (p. value> 0.05). In conclusion, knowledge and the role of health workers had no effect on the high risk behavior of contracting HIV / AIDS among ship crew. Keywords: Crew, Behavior, High Risk